Current Population Survey, April 1985: Veterans Supplement ([Verlag nicht ermittelbar], 1989)
This dataset provides information on labor force activity for the week prior to the survey. Comprehensive data are available on the employment status, occupation, and industry of persons 14 years old and over. Also included are personal characteristics such as age, sex, race, marital status, veteran status, household relationships, educational background, and Spanish origin. In addition, the supplement provides information on military service and veteran disability for males 18 years and older. Data include veteran status, period of service, Vietnam theater status, service-connected disability rating, and receipt of disability income.